Design and construction of an intermediate-scale fire resistance furnace, with commissioning and validation on a novel composite floor system - Fourie, Stephen Junior (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.